The Effect of Local Government Expenditure and Economic Growth on the Poverty Rate in North Sumatra Province - Rania Rizqi Ananda; Miftha Rizkina (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of local government expenditure and economic growth on the poverty rate in North Sumatra Province during the 2020–2024 period. The data used were secondary data obtained from the Statistics Indonesia (BPS) of North Sumatra Province and the Directorate General of Fiscal Balance (DJPK). The analytical method applied was multiple linear regression. The results showed that partially, local government expenditure had a significant negative effect on the poverty rate, meaning that an increase in government expenditure could reduce poverty. Meanwhile, economic growth had no significant effect on the poverty rate. Simultaneously, both independent variables explained 89.7% of the variation in the poverty rate, while the remaining percentage was influenced by other factors outside the model. This study concludes that local government expenditure plays an important role in poverty alleviation in North Sumatra Province. Therefore, the government should improve budget allocation effectiveness in productive sectors and social programs.